Ziyuglycoside I attenuates collagen-induced arthritis through inhibiting plasma cell expansion. (10th August 2022) - Sun, Hanfei; Wang, Manman; Su, Tiantian; Guo, Paipai; Tai, Yu; Cheng, Huijuan; Zhu, Zhenduo; Jiang, Chunru; Yan, Shangxue; Wei, Wei; Zhang, Lingling; Wang, Qingtong
Abstract: Ethnobotanical relevance: With most of the anti-rheumatic drugs having severe adverse drug reactions and poor tolerance, the active components from natural herbs provides a repository for novel, safe, and effective drug development. Sanguisorba officinalis L. exhibits definite anti-inflammatory capacity, however, whether it has anti-rheumatic effects has not been revealed. Aim of the study: In the present study, the effect of Ziyuglycoside I (Ziyu I), one of the most important active components in Sanguisorba officinalis L., was investigated in treating collagen-induced arthritis (CIA), illuminating its potential pharmacological mechanisms. Material and methods: CIA mice were treated with 5, 10, or 20 mg/kg of Ziyu I or 2 mg/kg of MTX, and clinical manifestations as well as pathological changes were observed. T and B cell viability was determined using cell counting kit-8, plasma autoantibodies and cytokines were tested with ELISA, T and B cell subsets were identified by flow cytometry, Blimp1 expression was detected by RT-qPCR and in situ immunofluorescence. The expression of activation-induced cytidine deaminase (AID) was detected by immunohistochemistry. ERK activation in B cells was verified through western blotting and immunofluorescence. Meanwhile, bioinformatics retrieval and molecular docking/molecular dynamics were used to predict the relationship between Blimp1, ERK and Ziyu I with the pharmacokinetics and toxicity of Ziyu I being evaluated in the ADMETlab Web platform. Results: Ziyu I treatment effectively alleviated the joint inflammatory manifestation including arthritis index, global scores, swollen joint count and body weight of CIA mice. It improved the pathological changes of joint and spleen of arthritic mice, especially in germinal center formation. Ziyu I displayed a moderate regulatory effect on T cell activation, the percentage of total T and helper T cells, and tumor necrosis factor-α, but transforming growth factor-β was not restored. Increased spleen index, B cell viability and plasma auto-antibody production in CIA mice were significantly reduced by Ziyu I therapy. Of note, we found that Ziyu I administration substantially inhibited the excessive expansion of plasma cells in spleen through preventing the expression of B lymphocyte induced maturation protein 1 (Blimp1) and AID in B cells. Ziyu I was predicted in silico to directly interact with ERK2, and reduce ERK2 activation, contributing to the depressed expression of Blimp1. Moreover, Ziyu I was predicted to have a favorable pharmacokinetic profile and low toxicity. Conclusion: Ziyu I effectively ameliorates CIA in mice by inhibiting plasma cell generation through prevention of ERK2-mediated Blimp1 expression in B cells. Therefore, Ziyu I is a promising candidate for anti-arthritic drug development. Graphical abstract: Image 1